2024
DOI: 10.1002/csc2.21176
|View full text |Cite
|
Sign up to set email alerts
|

Biochar application improves the yield, lodging resistance, and lignin synthesis mechanism in rice

Diankai Gong,
Zhengjin Xu,
Wenjing Zheng
et al.

Abstract: Biochar application elicits positive environmental and agricultural impacts owing to its physicochemical properties; however, the mechanism of biochar in regulating the lodging resistance in rice remains unclear. The present study was conducted to investigate the effects of biochar application on rice yield, lodging‐related traits, and enzymes activity and gene expression related to lignin biosynthesis in two rice (Oryza sativa L.) cultivars, that is, Shennong 265 and Akihikari. The biochar treatments were: 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…In this study, it was identified that although the newly created restorer line R382 has higher plant height and fresh weight above-ground, its lodging index is significantly lower mainly due to stronger stem strength compared to Huazhan (Figures 1, 4 and 6, Supplemental Table S1). It is certainly uncontroversial that the main parameter characterizing stem strength, bending moment at breaking (M), is positively correlated with the outer diameter of the basal stem, culm thickness, sectional modulus, bending stress, and the content of the various chemical constituents that make up the cell wall (Figures 6, S2 and S3), since all of these traits will result in enhanced stalk strength [19,26,41,58]. Our results are similar to those of the previous study on the effect of nitrogen fertilizer application, in which it was found that an increase in nitrogen application led to a reduction in culm thickness, and changes in the number and area of vascular bundles, resulting in less lignin and cellulose deposition, an increase in the hollow area of the stem, and a higher likelihood of lodging in rice [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, it was identified that although the newly created restorer line R382 has higher plant height and fresh weight above-ground, its lodging index is significantly lower mainly due to stronger stem strength compared to Huazhan (Figures 1, 4 and 6, Supplemental Table S1). It is certainly uncontroversial that the main parameter characterizing stem strength, bending moment at breaking (M), is positively correlated with the outer diameter of the basal stem, culm thickness, sectional modulus, bending stress, and the content of the various chemical constituents that make up the cell wall (Figures 6, S2 and S3), since all of these traits will result in enhanced stalk strength [19,26,41,58]. Our results are similar to those of the previous study on the effect of nitrogen fertilizer application, in which it was found that an increase in nitrogen application led to a reduction in culm thickness, and changes in the number and area of vascular bundles, resulting in less lignin and cellulose deposition, an increase in the hollow area of the stem, and a higher likelihood of lodging in rice [20].…”
Section: Discussionmentioning
confidence: 99%
“…The stem strength of the basal internodes is identified as one of the most important traits associated with lodging resistance in rice [16,17,21,23,24], along with culm diameter, culm thickness, the thickness of mechanical tissues, and the number and area of vascular bundles [21,24,25]. In addition, the mechanical strength of basal internodes depends mainly on their chemical composition, such as silicon, and the content of non-structural and structural carbohydrates (mainly lignin, cellulose, and hemicellulose) [26][27][28][29]. In general, well-arranged internode length, a low center of gravity height, a high proportion of structural carbohydrates such as lignin and cellulose in the stalks, and short and thick basal internodes with more vascular bundles, positively contribute to the lodging resistance in rice [9,30].…”
Section: Introductionmentioning
confidence: 99%